Telok Abang Ship Culture: A Symbol of Pride for Palembang Residents on Independence Day - Marsinah, Marsinah; Hatidah, Hatidah; Fitri Indriani, R.A Rodia; Purwanto, M Bambang (PT FORMOSA CENDEKIA GLOBAL, 2024)
Community Service activities carried out by four lecturers of the Prasetiya Mandiri Polytechnic play a crucial role in the preservation of Palembang City culture and tourism, especially the Telok Abang Ship tradition related to the commemoration of Independence Day on August 17. This program prioritizes collaboration between the academic world and the community in preserving and promoting Palembang's rich cultural heritage. The Telok Abang ship is not only a cultural symbol, but also an important part of the identity and pride of the people of Palembang. The involvement of the younger generation in this preservation shows a strategic effort to instill awareness about the importance of preserving local culture and strengthening the spirit of nationalism. In addition, this activity shows the significant contribution of universities in supporting the preservation of local culture and tourism through community service programs. Thus, this program is not only successful in preserving cultural traditions, but also in developing local tourism and strengthening national identity.